Conflict after the Cold War arguments on causes of war and peace - Betts, Richard K. (Pearson, 2013)
Conflict After the Cold War is a classic and first-rate reader that addresses enduring problems of international security and admirably represents a variety of theoretical orientations without overreliance on contemporary squabbles. By including classical and current readings, it helps students understand the important ideas-not just the names-behind theories of war and peace.